2021
DOI: 10.1093/icb/icab121
|View full text |Cite
|
Sign up to set email alerts
|

How an Early, Inclusive Field Course can Build Persistence in Ecology and Evolutionary Biology

Abstract: Field courses have been identified as powerful tools for student success in science, but the potential for field courses to address demographic disparities and the mechanisms behind these benefits are not well understood. To address these knowledge gaps, we studied students in a non-majors Ecology and Evolutionary Biology course, Introduction to Field Research and Conservation, at the University of California Santa Cruz (UCSC), a large Hispanic-Serving Institution. We examined (a) the effects of participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
1
10
2
Order By: Relevance
“…Prioritize inclusive teaching practices in conservation courses by embracing the tenets of inclusive course design, active learning modalities and service learning techniques, to encourage broader participation and interest in conservation sciences. Recommended reading [64][65][66][67].…”
Section: Racism In Conservation Science and Practice Todaymentioning
confidence: 99%
“…Prioritize inclusive teaching practices in conservation courses by embracing the tenets of inclusive course design, active learning modalities and service learning techniques, to encourage broader participation and interest in conservation sciences. Recommended reading [64][65][66][67].…”
Section: Racism In Conservation Science and Practice Todaymentioning
confidence: 99%
“…We found that course features that supported inclusion (Zavaleta et al 2020), provided holistic support, focused on community building (Race et al 2021), and allowed for multiple inquiry‐driven group research opportunities created spaces for student gains in the above‐mentioned affective outcomes. When designing field course experiences, we suggest attention be paid to the “5 I’s”‐ Inclusion, Immersion, Interpersonal, Iteration, and Inquiry‐driven‐ to support psychological outcomes associated with persistence in the sciences (Race et al, 2021). Additionally, we argue for a flipped curricular structure in biology majors—one that puts research at the front of the major experience—as a tool to improve retention in and diversify ecology and evolutionary biology.…”
Section: Emerging Researchmentioning
confidence: 99%
“…David Esparza and Kira Treibergs.-In 2012, the 2012 called for research to define the affective domain in field-based learning. In response, recent studies suggest that field courses in ecology and evolutionary biology (EEB) can support students' affective development (Beltran et al 2020, Race et al 2021). However, it has also been found that minoritized students in EEB programs can express discomfort in the outdoors (O'Brien et al 2020).…”
Section: Describing Student Affect In Biological Field Courses Throug...mentioning
confidence: 99%
See 2 more Smart Citations